Standardisasi Simplisia Kulit Buah Mangga (Mangifera Indica L.) Varietas Gadung - Andini Andini; Cindy Fernanda Putri (LPPMKI - AKAFARMA AKFAR PIM, 2021)
Mango peel (Mangfera indica L.) has many pharmacological effects as a traditional medicine. Therefore, standardization of mango peel simplisia needs to be done as a preparation of phytopharmaca raw material. This research aimed to obtain standardization of mango peel simplisia include specific and non-specific parameter. The research procedures include plant determination, simplisia preparation as well as specific standardization test (includes organoleptic, water-soluble compound concentration, and ethanol solution compound concentration) and nonspecific standardization test (includes moisture content, dried shrinkage, total ash content and acid insoluble ash content). The specific organoleptic parameters of dried mango peel simplisia have a distinctive sweet aroma, bitter taste, and brownish yellow colour. Water-soluble and ethanol-soluble concentrations are 22,36% ± 1,17% and 9,56% ± 0,07%. Moisture content is 9,09% ± 1,44%. Dried shrinkage rate is 0,19% ± 0,04%. Total ash and acid insoluble ash contents are 4,11% ± 0,10% and 0,14% ± 0,03%. The mango peel simplisia has met the quality standard of the raw material.